Situating animal ethics in Thai elephant tourism. (10th October 2019) - Cui, Qingming; Xu, Honggang
Abstract : Following ethical contextualism, this article situates different animal ethical principles, from anthropocentrism to non‐anthropocentrism and relational caring ethics, in Thai social contexts in order to examine whether these principles can lead to a sustainable ethical practice in elephant conservation. The results show that, as non‐anthropocentrism, animal rights ethics are impractical in Thailand because of temporal, spatial, economic and social constraints. As weak anthropocentrism, animal welfare ethics endorse the tourism industry to commercialise the encounter value of elephants by developing elephant camps. Along with animal welfare, relational ecofeminism justifies the emerging model of elephant sanctuaries. Both camp and sanctuary models create a work‐for‐care cycle, in which elephants work to generate economic gains, some of which are in turn used to care for elephants. However, because of evolving social situations, such as potential market competition and poaching of wild elephants, the morality of the work‐for‐care cycle is weak and can be challenged. Nevertheless, sanctuaries offer a direction for a local solution because of their potentially responsible business model. In conclusion, there is not a single set of ethics that can solve all problems and be sustainable in all contexts.